1968
DOI: 10.1530/acta.0.0590555
|View full text |Cite
|
Sign up to set email alerts
|

Post Heparin Plasma Lipoprotein Lipase Activity in Thyroid Disease

Abstract: Plasma post heparin lipoprotein lipase activity (LLA) has been studied in patients with hyper- and hypothyroidism and in rabbits made thyrotoxic with thyroxine. The hypothyroid patients had high triglyceride and low LLA values as compared with a control group of healthy subjects. Statistically highly significant negative correlation was found between the triglycerides in fasting patients and the post heparin LLA, indicating a causal relationship, possibly with disturbance of chylomicron degradation due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
1

Year Published

1972
1972
1993
1993

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 0 publications
1
11
0
1
Order By: Relevance
“…Other than a slight increase in perfusate flow rate (P < 0.01) in livers from animals treated with 10 ,ug TJ100 g body wt per d for 7 d, perfusion parameters were similar to the controls, perfusate flow rate was 3.0±0.2 ml/min per g liver in livers from the control rats and 3.9+0.1 ml/min per g liver for T3 treated aniiimals. All perfusion parameters were similar for animals treated with either T3 or PTU for only 3 …”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Other than a slight increase in perfusate flow rate (P < 0.01) in livers from animals treated with 10 ,ug TJ100 g body wt per d for 7 d, perfusion parameters were similar to the controls, perfusate flow rate was 3.0±0.2 ml/min per g liver in livers from the control rats and 3.9+0.1 ml/min per g liver for T3 treated aniiimals. All perfusion parameters were similar for animals treated with either T3 or PTU for only 3 …”
Section: Resultsmentioning
confidence: 84%
“…INTRODUCTION Alterations in thyroid status appear to be associated with changes in serum triglyceride concentrations. In human hyperthyroidism, decreased (1), normal (2)(3)(4), and increased (5) serum concentrations of triglyceride have been observed. Concentrations ofserum triglyceride, although usually elevated in human hypothyroidism (1)(2)(3)(5)(6)(7)(8)(9), have also been reported to be normal (10,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is in sharp contrast to the situation in cholesterol metabolism, which is well explored in both hyper-and hypothyroidism and is generally believed to undergo typical and consistent changes in both conditions. The plasma triglyceride concentration may be completely normal in hypothyroidism (1,2), but usually it is moderately elevated (2)(3)(4)(5) and occasional cases of gross hyperlipemia have been reported in myxedema (1,2,6). The increase has been attributed to a low lipoprotein lipase (LPL) activity, since it has been shown that the postheparin plasma lipolytic activity (PHLA) is inversely corre-'Abbreviations used in this paper: LDL and VLDL, low density and very low density lipoprotein, respectively; LPL, lipoprotein lipase; PBI, protein-bound iodine; PHLA, lipolytic activity of postheparin plasma; RBW, relative body weight; T3, triiodothyronine uptake by resin; TG, triglyceride.…”
Section: Introductionmentioning
confidence: 99%
“…Unter dem Einfluß von Schilddrüsenhormonen kommt es zu einer Verände rung der Plasma-Spiegel von Cholesterin und Neutralfetten (JACOBSEN, 1973;KIRKEBY, 1969;NIKKILA LL KEKKI, 1972;WIELAND U. SEIDEL, 1972 Bei der Schilddrüsen-Überfunktion werden übereinstimmend erhöhte Nüch ternwerte der freien Fettsäuren im Plasma angegeben (AVOGARO etal, 1965;CLAYTON U. BIERMAN, 1959;DIETERLE etal., 1969;DOAR etal, 1969;EATON et al, 1965;FELT, 1967;HALES U. HYAMS, 1964;HARLAN etal., 1963;JAHNKE et ai, 1965;LEVY et al, 1970;MARKS et al, 1960;RICH et al, 1959;SANDHOFER et al, 1966aSANDHOFER et al, , 1966bSANDHOFER et al, , 1967bVINIK et al. 1970;WOEBER et al, 1966).…”
Section: C) Lipolyse Und Fettstoffwechselunclassified